2014
DOI: 10.2147/dddt.s67941
|View full text |Cite
|
Sign up to set email alerts
|

The role of ketotifen in the prevention of testicular damage in rats with experimental unilateral undescended testes

Abstract: The aims of this study conducted on rats were to determine mast cell (MC) proliferation on undescended testes (UDTs); whether there is a correlation between MC proliferation and testicular damage; and whether testicular damage can be prevented with administration of an MC blocker. Sixty-five newborn male rats were divided into three groups. During the neonatal period, unilateral UDTs were experimentally induced in Group 2 and Group 3. The rats in Group 3 were given 1 mg/kg/day ketotifen orally until the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Here, the serine protease tryptase enhances fibroblast proliferation and collagen synthesis, inducing fibrosis of the seminiferous tubules (62). MC might also regulate fibrosis by activating matrix metalloproteinases (MMP) and tissue MMP inhibitors (63).…”
Section: Mast Cellsmentioning
confidence: 99%
“…Here, the serine protease tryptase enhances fibroblast proliferation and collagen synthesis, inducing fibrosis of the seminiferous tubules (62). MC might also regulate fibrosis by activating matrix metalloproteinases (MMP) and tissue MMP inhibitors (63).…”
Section: Mast Cellsmentioning
confidence: 99%
“…This may provide an invaluable source of autologous male gametes for treating male infertility in azoospermic patients. Acikgoz et al 63 have demonstrated that the number of mast cells are increased in interstitial and sub-tubular locations in rats with unilateral cryptorchidism resulting in fibrosis and deterioration of spermatogenesis. Ketotifen, a mast cell blocker was effective in interruption of this process of inflammation and fibrosis before and after surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 22 One possible reason may be the pretreatment KFs with the supernatants of mast cells. In the supernatant, there are various enzymes, cytokines 10 , 44 49 (such as interleukin, GM-CSF [granulocyte-macrophage colony-stimulating factor], bFGF [basic fibroblast growth factor], TGF-β, and TNF-α), and active material (histamine, heparin, platelet activating factor, proteoglycan, etc). They may have actions on fibroblasts to regulate the expression of the relevant protein participating in fibrosis.…”
Section: Discussionmentioning
confidence: 99%